Associations between biomarkers of prenatal metals exposure and non-nutritive suck among infants from the PROTECT birth cohort in Puerto Rico - Kim, Christine; Zimmerman, Emily; Huerta-Montañez, Gredia; Rosario-Pabón, Zaira Y.; Vélez-Vega, Carmen M.; Alshawabkeh, Akram N.; Cordero, José F.; Meeker, John D.; Watkins, Deborah J. (Frontiers in Epidemiology, 2022)
Background/Aim: Infant non-nutritive suck (NNS) has been used as an early marker of neonatal brain function. Although there is an established relationship between prenatal exposure to certain metals and brain development, the association between metal exposure and NNS has not been explored. Therefore, in this study we assessed associations between maternal urinary metal(loid) concentrations and NNS measurements among infants from the Puerto Rico PROTECT birth cohort. We hypothesized that maternal urinary metal(loid) concentrations are significantly associated with infant NNS measures in a sex-dependent manner. Methods: We measured urinary concentrations of 14 metal(loid)s in pregnant women at up to three time points in pregnancy. The geometric mean of each metal(loid) for each pregnant woman was calculated and used as an exposure measurement across gestation. NNS measurements (duration, frequency, amplitude, bursts/min, cycles/burst, cycles/min) were collected from infants between 4-6 (± 2 weeks) weeks of age using our custom research pacifier. Linear regression was used to estimate associations between urinary metal(loid) concentrations across pregnancy and continuous NNS variables. Sex-specific effects were estimated using interaction terms between NNS variables and infant sex. Results: We observed significant positive associations between mercury, manganese, and tin with NNS duration and NNS cycles/burst. Furthermore, the association between NNS cycles/min with cadmium, manganese, and tin were in the opposite direction from its association with zinc, as well as with copper. For the sex-stratified analysis, the negative associations between metal(loid)s and NNS duration were predominantly driven by male infants; however, the negative associations between metal(loid)s and NNS bursts/min were mainly driven by female infants. Conclusion: We observed significant associations between prenatal metal(loid) exposure and NNS measurements among infants from the ongoing Puerto Rico PROTECT cohort. Similar to previous studies that have demonstrated associations between NNS and subsequent neurodevelopment, this study highlights the potential of NNS as a quantitative index to measure altered neurodevelopment from prenatal metal(loid) exposures. We believe this study will inform future efforts aimed at reducing health risks related to early life metal exposures, such as developing early identification of metal-induced adverse outcomes in child neurodevelopment.